Consumer Protection Against the Sale of Counterfeit Products in E-Commerce: A Human Rights and Legal Certainty Perspective in Indonesia - Santiago, Owen; Situmeang, Ampuan; Nurlaily, Nurlaily (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
The phenomenon of e-commerce in Indonesia has demonstrated rapid growth, with high transaction values projected in 2024. However, the circulation of counterfeit products on digital platforms poses a serious challenge, endangering consumers. Although the legal framework for consumer protection in Indonesia provides a foundation for safeguarding consumer rights, oversight of counterfeit products in e-commerce has been deemed ineffective in ensuring consumer protection. This study employs normative legal research methods with comparative law, legislative, and conceptual approaches. The findings reveal that the Consumer Protection Act (UU Perlindungan Konsumen) has not been fully effective in ensuring the accountability of digital platforms, monitoring products, and resolving disputes. In comparison, EU regulations mandate the responsibility of digital platforms, the use of tracking technologies such as blockchain, regular audits, and strict sanctions for violations. The study recommends strengthening platform accountability in seller verification, adopting technology for product monitoring, and developing an integrated online dispute resolution mechanism through the Consumer Dispute Settlement Body (BPSK). Referring to progressive legal theory, Indonesia's regulatory framework must adaptively evolve to address digital dynamics, create legal certainty, and build public trust in a secure and equitable e-commerce ecosystem. [Fenomena e-commerce di Indonesia telah menunjukkan pertumbuhan pesat dengan nilai transaksi yang tinggi pada tahun 2024. Namun, peredaran produk palsu di platform digital menjadi tantangan serius yang membahayakan konsumen. Meskipun kerangka hukum perlindungan konsumen di Indonesia telah memberikan landasan hukum untuk melindungi hak konsumen, namun pengawasan terhadap produk palsu di e-commerce dinilai belum efektif dalam melindungi kosnumen. Metode penelitian yang digunakan adalah penelitian hukum normatif dengan pendekatan perbandingan hukum, perundang-undangan, dan konseptual. Hasil penelitian menunjukkan bahwa UU Perlindungan Konsumen belum optimal dalam memastikan tanggung jawab platform digital, pengawasan produk, dan penyelesaian sengketa. Sebagai perbandingan, regulasi UE mengatur kewajiban platform digital, penggunaan teknologi pelacakan seperti blockchain, audit berkala, dan sanksi tegas bagi pelanggar. Rekomendasi penelitian mencakup penguatan tanggung jawab platform dalam verifikasi penjual, adopsi teknologi untuk pengawasan produk, dan pengembangan mekanisme penyelesaian sengketa daring yang terintegrasi dengan Badan Penyelesaian Sengketa Konsumen (BPSK). Dengan mengacu pada teori hukum progresif, regulasi di Indonesia perlu berkembang secara adaptif untuk menghadapi dinamika digital, menciptakan kepastian hukum, dan meningkatkan kepercayaan masyarakat terhadap e-commerce yang aman dan berkeadilan].